The normative challenge of interaction: justice conflicts in democracy promotion - Poppe, Annika Elena; Wolff, Jonas (2012)
Abstract: In the global "North-West", liberal democracy is regarded as the universally valid model of political rule that is to be promoted globally via foreign and development policies. Democracy promotion, however, is frequently challenged by justice-related claims. Whereas external democracy promoters refer to democracy's universal value, those resisting democracy promotion point to the collective entitlement to a self-determined political evolution. "North-Western" governments see liberal democracy as the only embodiment of a just political order, but in those countries that are the targets of democracy promotion different understandings of appropriate norms and institutions may exist. And even if democracy is generally regarded as the best formula to construct a just polity, democratization at times is perceived as threatening intra-state peace, an equally valued goal. Contestation about democracy promotion has, therefore, a crucial normative dimension that can be conceptualized as a se